Helping a Child with Autism Spectrum Disorder Cope with Divorce. Issue 4 (May 2018) - Reilly, Marie; Fogler, Jason; Bridgemohan, Carolyn; Wiley, Melora; Weitzman, Carol; Augustyn, Marilyn
Abstract : CASE: Aaron is an 11-year-old boy with autism spectrum disorder (ASD), with cognitive and language skills in the above-average range, whose parents have recently separated. Aaron's mother initiated the separation when she learned that Aaron's father had maintained a relationship with a woman with whom he has a 10-year-old daughter. When Aaron's mother discovered this relationship, she demanded that Aaron's father leave their home. Aaron's father has moved in with his long-term girlfriend and keeps in contact with Aaron by calling once a day. Neither Aaron's father nor mother has discussed the reason for their separation with Aaron. So far, they have explained their separation by telling Aaron that they are "taking a break." Aaron's mother has been deeply hurt by Aaron's father's infidelity and does not want to reconcile with him. Aaron's father recognizes this but would like to continue to have a close relationship with his son. He would also like Aaron to get to know his half-sister. Aaron's mother seeks guidance regarding how to talk to Aaron about the separation and his father's second family. Given Aaron's diagnosis of ASD, she is particularly concerned about his ability to cope with this unexpected change in circumstances. What is your advice?